Dinâmica populacional e de empregos nos centros urbanos das metrópoles brasileiras - Vanessa Gapriotti Nadalin; Matheus dos Santos Rabetti; Cléo Alves Pinto de Oliveira; Bernardo Alves Furtado; Carolina Baima Cavalcanti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper presents the results of the research project carried over by the Ministry of Cities and the Institute of Applied Economic Research, entitled "Central urban areas of Brazilian cities". The research investigates the population and employment dynamics in central urban areas of twelve selected capitals. Thus, central areas are conceptualized and delimited for each city. Their perimeters are then made compatibility with the census tracts for the years 1991, 2000 and 2010. The analysis of the dynamics of jobs was based on Kernel heat maps, using data from the Annual Social Information of the Ministry of Labor for the years 2003 and 2012. These analyses allowed the definition and concept of centralities and its comparison with the central areas. The main methodological contribution of the research is the analysis of georeferenced intraurban jobs. However, it is clarifying that the availability of the database impeded the analysis of public positions Results indicate that there is loss of population in central areas for the period 1991-2000. However, recovery of population is observed in the next decade. Jobs decentralization over urban tissue is verified for the period 2003-2012. Indications of future research are also presented.
Keywords: R12; J6; C14; 330; metropolitan regions; intraurban jobs; urban central areas; population mobility; urban centers; kernel density